Debit card and demand for cash - David, Bounie; Abel, François; Patrick, Waelbroeck (Journal of Banking & Finance, 2016)
Despite the growing importance of the debit card in most developed countries, there are relatively few academic studies that analyze the impact of such evolution on the demand for cash. Beyond data availability, this research is complicated by the fact that the debit card provides two services for consumers - cash withdrawal and payment - that have contrasting effects on cash holdings and cash usage. Using micro-level data, we estimate the impacts of both services on the demand for cash by comparing the cash holdings and cash usage of three populations, namely non-cardholders, ATM-only cardholders, and debit cardholders. Controlling for various individual and network characteristics as well as a possible endogeneity issue, we find that the negative effect of the payment service on the demand for cash dominates the positive effect of the cash withdrawal service resulting in an overall negative impact of the debit card on the demand for cash.